Survivability of Vibrio parahaemolyticus in satar and otak-otak, Malaysian fish-based street food - Tang, John Yew Huat; Mat Sa'ad, S. H.; Banerjee, S. K.; Ho, L. H.; Radu, Son (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Street food is popular in Asia due to its availability, low price and good taste. The safety of street food has been always questionable due to its poor handling which probably leads to microbial contamination. The objective of this study was to determine the surviving quantities of V. parahaemolyticus under various conditions in street-vended food, namely satar and otak-otak after anticipated cross-contamination to support policy and regulatory documents. The satar and otak-otak were prepared from minced and unminced fish flesh, respectively, together with other ingredients. Each satar and otak-otak were prepared with 0, 0.5, 1.5 and 3% of sodium chloride (NaCl), respectively. V. parahaemolyticus inoculum at approximately 8.66 log CFU/ml were inoculated into the samples and incubated for up to 6 h. Samples were taken at 0, 1, 3 and 6 h for enumeration of V. parahaemolyticus using spread plate method on Thiosulphate Citrate Bile Salts Sucrose (TCBS) agar. For control samples, V. parahaemolyticus was not immediately inactivated in distilled water even though significant better survivability was observed in Phosphate Buffer Saline (PBS). The numbers of V. parahaemolyticus was found to decrease by varying amounts based on the salt content and duration of holding. However, significant amounts survived to indicate potential risk.